Soil disturbance caused by ground-based skidding at different soil moisture conditions in Northern Iran. Issue 3 (1st September 2016) - Naghdi, Ramin; Solgi, Ahmad; Zenner, Eric K.; Tsioras, Petros A.; Nikooy, Mehrdad
ABSTRACT: Skidding operations induce considerable and wide spread soil disturbance. It is unclear how much additional damage is caused by increased soil moisture content at the time of skidding. We visually assessed 16 categories of soil surface disturbances, measured surface layer bulk density, porosity, and rutting in two oriental beech sites in northern Iran following five frequencies of traffic on two slope gradients with 19% and 33% soil moisture content. At both moisture contents, the most severe soil disturbances occurred with more frequent equipment traffic and on steeper slopes. Soil disturbances were detected on 65% of the harvested area at lower and 87% at higher moisture content. Bulk density, porosity, and rut depth were significantly affected by traffic frequency, trail slope and moisture content. Bulk density nearly reached critical values of 1.4-1.55 g cm –3 after 7 passes at higher and 12 passes at lower moisture content. Adverse effects on porosity caused by increased traffic and trail slope increased with increasing soil moisture content. Rutting was observed after one and seven passes at high and low moisture content, respectively, and was deeper on steeper slopes. To minimize disturbance, ground-based skidding should be limited to times when soil moisture content is low.